A study of hip arthroplasty using bipolar endo-prothesis for fracture neck of femur - Sakthivel, Rajarajan Nagu; Subramanyam, Balaji Ponna puvula; Balakrishnan, Vijayan (International Journal of Research in Medical Sciences, 2016)
Background: The purpose of this study is to analyze 20 cases of bipolar hip arthroplasty done for fracture neck of femur from August 2011 to January 2013. The technique, overall functional results were tabulated in a proforma and analyzed, complications if any were noted and analysed. A conventional Austin Moore and Thompson device has been routinely deployed, however in long term follow-up, unsatisfactory results remained high due to femoral stem loosening, acetabular erosion, intrusion of prosthesis into the pelvis and difficulties with total hip revisions. These factors led to the development of bipolar prosthesis. Methods: 20 patients were operated by cemented bipolar hemiarthraoplasty for fracture neck of femur. All the patients had displaced fracture neck of femur and were in the elderly age group. Results: 20% of the patients had excellent results and 80% had good results. There was a significant incidence on the postoperative functional out come. There was a significant increase in the postoperative score by 4 grades. Conclusions: For elderly patients with fracture neck of femur cemented bipolar hemiarthroplasty gives good functional outcome, except for some difficulties in routine daily activities like sitting cross legged and squatting.